First-Principles Studies for Electronic Structure and Optical Properties of Strontium Doped β-Ga2O3 - Loh Kean Ping; Mohd Ambri Mohamed; Abhay Kumar Mondal; Mohamad Fariz Mohamad Taib; Mohd Hazrie Samat; Dilla Duryha Berhanuddin; P. Susthitha Menon; Raihana Bahru (Micromachines, 2021)
The crystal structure, electron charge density, band structure, density of states, and optical properties of pure and strontium (Sr)-doped β-Ga2O3 were studied using the first-principles calculation based on the density functional theory (DFT) within the generalized-gradient approximation (GGA) with the Perdew–Burke–Ernzerhof (PBE). The reason for choosing strontium as a dopant is due to its p-type doping behavior, which is expected to boost the material’s electrical and optical properties and maximize the devices’ efficiency. The structural parameter for pure β-Ga2O3 crystal structure is in the monoclinic space group (C2/m), which shows good agreement with the previous studies from experimental work. Bandgap energy from both pure and Sr-doped β-Ga2O3 is lower than the experimental bandgap value due to the limitation of DFT, which will ignore the calculation of exchange-correlation potential. To counterbalance the current incompatibilities, the better way to complete the theoretical calculations is to refine the theoretical predictions using the scissor operator’s working principle, according to literature published in the past and present. Therefore, the scissor operator was used to overcome the limitation of DFT. The density of states (DOS) shows the hybridization state of Ga 3d, O 2p, and Sr 5s orbital. The bonding population analysis exhibits the bonding characteristics for both pure and Sr-doped β-Ga2O3. The calculated optical properties for the absorption coefficient in Sr doping causes red-shift of the absorption spectrum, thus, strengthening visible light absorption. The reflectivity, refractive index, dielectric function, and loss function were obtained to understand further this novel work on Sr-doped β-Ga2O3 from the first-principles calculation.